A comprehensive review on performance, combustion and emission characteristics of biodiesel fuelled diesel engines. (November 2017) - Tamilselvan, P.; Nallusamy, N.; Rajkumar, S.
Abstract: Direct injection diesel engines are more popular in the automotive sector than spark ignition (SI) engines due to its fuel lean operation. However, the demand of fossil fuel is rising day by day and hence the major fuel source of diesel engine, the petroleum based fuel, is depleting rapidly. Many countries depend mainly on imported fossil fuels due to lack of fuel reserves and it has great impact on the economy. In addition to this, the major concerns of diesel engine are its oxides of nitrogen and smoke emissions. Therefore, for the past several decades extensive efforts are being made to search for alternate fuels to overcome the dependence on fossil fuel and environment pollution. In this regard, several alternate fuels namely hydrogen, oxygenated fuels like alcohol fuels, dimethyl ether and biodiesel fuels etc., have been extensively analysed. Recent studies show that biodiesel is one of the most promising alternate fuels for diesel engines because of its biodegradable, oxygenated, sulphur free and renewable characteristics. Hence, it is getting the attention of researchers all over the world. The blends of biodiesel with fossil diesel have many benefits like reduction in emissions, lower engine wear, lesser engine oil consumption and comparable thermal efficiency vis-a-vis diesel fuel. Exhaustive experimental works have been carried out to analyse the suitability of biodiesel fuel as alternate fuel and to explore their advantages in diesel engines. Hence, this paper is attempted to present a comprehensive review on the performance, combustion and emission characteristics of some important biodiesel fuels on diesel engines. This comprehensive review on the published literature will be helpful to the researchers to understand the state-of-the-art technology of the biodiesel fuelled compression ignition engine.